Observations on the laboratory culture of the harpacticoid copepod Euterpina acutifrons (Dana, 1847) using different diets - Jasmine, S.; George, Rani Mary; Lazarus, S. (Indian Journal of Fisheries, 2016)
Hatching success, nauplii production, maturation and survival of the harpacticoid copepod Euterpina acutifrons (Dana, 1847) fed on mono/mixed culture of Isochrysis galbana, Tetraselmis gracilis, Chaetoceros calcitrans and Chlorella marina were studied. The time taken for E. acutifrons to mature was the lowest with a diet of I. galbana followed byÂ C. calcitrans. Percentage of survival was highest with a mixed diet of 75% I. galbana and 25% C. calcitrans (84%) followedÂ by T. gracilis (68%). The study also revealed that both feed type and concentration played significant role in production and survival of E. acutifrons. Mixed diet of I.galbana and C. calcitrans showed maximum adult production followed by a diet of T.gracilis. The mean values of all the three stages of the copepod viz., adults, ovigerous females and copepodite-nauplii were found much greater in the treatment with replacement of the culture medium and feed. Mass culture using different organic feeds was also carried out and it was found that mean growth in terms of adult stage production was found to be higher when fed with rice bran followed by groundnut oil cake (GOC) and the least in cow dung treatment. In rice bran treatment, copepodites showed higher production rate when compared to the other two feeds. Mean growth in terms of nauplii production was also higher in rice bran fed group followed by GOC fed group and the least in cow dung treatment.